2007
DOI: 10.1007/s00429-007-0162-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vestibular nerve section on the expression of the hyaluronan in the frog, Rana esculenta

Abstract: Following postganglionic lesion of the eighth cranial nerve, the changes in the expression of hyaluronan (HA), one of the extracellular matrix macromolecules, were examined in the medial (MVN) and lateral (LVN) vestibular nuclei and in the entry or transitional zone (TZ) of the nerve in the frog. HA was detected in different survival times by using a specific biotinylated hyaluronan-binding probe. HA expression was defined by the area-integrated optical density (AIOD), calculated from pixel intensities of digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
(126 reference statements)
1
3
0
Order By: Relevance
“…The possible explanations of the differences are described above. The present results, along with previous works (Halasi et al, 2007;Deak et al, 2012, Gaál et al, 2014Faralli et al, 2016;Ma et al, 2019), may contribute to understanding the function of the ECM in the mechanisms of vestibular plasticity during the restoration of impaired vestibular function. Although data are presently available on CSPG, hyaluronan, tenascin-R and brevican, the common finding of these experiments is that unilateral labyrinthectomy induces a temporary decline in the expression of the PNN related ECM molecules in the vestibular nuclei, which process is followed by an elevated expression simultaneously with the repair of the vestibular functions.…”
Section: Discussionsupporting
confidence: 78%
“…The possible explanations of the differences are described above. The present results, along with previous works (Halasi et al, 2007;Deak et al, 2012, Gaál et al, 2014Faralli et al, 2016;Ma et al, 2019), may contribute to understanding the function of the ECM in the mechanisms of vestibular plasticity during the restoration of impaired vestibular function. Although data are presently available on CSPG, hyaluronan, tenascin-R and brevican, the common finding of these experiments is that unilateral labyrinthectomy induces a temporary decline in the expression of the PNN related ECM molecules in the vestibular nuclei, which process is followed by an elevated expression simultaneously with the repair of the vestibular functions.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, enzymatic removal of hyaluronan-based pericellular matrix increases extrasynaptic AMPA receptor diffusion and the exchange of synaptic receptors, modulating short-term synaptic plasticity (Frischknecht et al 2009). Intriguingly, PNN number and staining intensity are restored in coincidence with the compensation of postural vestibular functions (see also Halasi et al 2007;Deák et al 2012). PNN restoration may thus contribute to the stabilisation of the re-wired neuronal connections which may underlie behavioural recovery.…”
Section: Perineuronal Net Changes In the Lvn During Vestibular Compenmentioning
confidence: 95%
“…For example, exposure to an enriched environment induces significant axonal remodelling in the cerebellar nuclei and enhances visual cortex plasticity, in parallel with a conspicuous reduction of PNNs (Sale et al 2007;Foscarin et al 2011). PNNs are also diminished during injury-induced neuritic remodelling (Carmichael et al 2005;Halasi et al 2007;Deák et al 2012;Carulli et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the biological activities are through the interaction between HA and its cell surface receptors, CD44, RHAMM, and ICAM-1 (intercellular adhesion molecules-1) ( 3 , 4 ). HA was also found to enhance peripheral nerve regeneration in the frog ( 5 ). In addition, several reports showed that HA possessed free radical scavenging and antioxidant activities in vivo and in vitro settings ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%